Proper Implementation of Laws and Policies: A Definitive Way for Providing Justice - Bhndaree, Roshi (Kathmandu School of Law Review, 2012)
The economic influence is the pushing and pulling factor for the commission of the crime of trafficking. The majority of the girls, women and children they have been trafficked in the recent days more in number because of the larger growing sex market. The easy money making, open border and criminalized and organized crime on one hand encourages the pimps and the perpetrators for the commission of the crime and to the other hand the search for the means of livelihood from the victim side contributes to larger extent for the crime. The effective implementation of the laws and plans and policies are the pre-requisites for the economic enhancement of the citizen which ultimately helps to controls the crime rate. The capability enhancement could be the ultimate way for the restoration of the economic standard of the victim to the society and administration of the justice.